Androgenic alopecia, premature graying, and hair thinning as independent predictors of coronary artery disease in young Asian males. Issue 4 (December 2017) - Sharma, Kamal; Humane, Dhammdeep; Shah, Komal; Patil, Sachin; Charaniya, Riyaz; Meniya, Jayesh
Abstract : Introduction: We herewith aimed to explore the association of premature graying, androgenic alopecia (AGA), and hair thinning with coronary artery disease (CAD) in young (⩽40 years) male individuals from Western India. Patients and methods: In this prospective, case–control study, 1380 male individuals from a super speciality cardiac care center were enrolled, of which 468 were established cases of CAD and 912 were age-matched healthy male individuals not having history of any major illness including CAD. Details of demographics, cardiovascular risk factors, and cutaneous markers were collected for both the groups. Results: Prevalence of hypertension (30.3 vs. 13.6%), obesity (28.8 vs. 12.2%), hair thinning (36.3 vs. 14.6%), premature graying (49.6 vs. 29.9%), AGA (49.1 vs. 27.4%), and lipid abnormalities (total cholesterol – 16.7 vs. 8.8%; low-density lipoprotein – 7.3 vs. 2.2%; and high-density lipoprotein – 92.5 vs. 88.7%) were higher in cases as compared with control. Multiple logistic regression analysis showed that AGA [5.619, 95% confidence interval (CI): 4.025–7.845, P <0.0001] is the strongest predictor of CAD among young Asian male individuals, closely followed by premature graying (5.267, 95% CI: 3.716–7.466, P <0.0001), obesity (4.133, 95% CI: 2.839–6.018, P <0.0001), and hair thinning (3.36, 95% CI: 2.452–4.621, P <0.0001). SYNTAX score, left ventricle ejection fraction, and degree of disease severity were also found to be independent associates of premature graying and AGA. Conclusion: Our findings support the hypothesis that cutaneous markers are independently associated with underlying CAD irrespective of other classical cardiovascular risk factors. This, in combination with classical markers, could be effectively used for early identification and risk stratification of young patients with occult or established CAD.